The Power Play: the Unseen Costs of Workplace Politics and Leadership Gaps (London Journal of Research In Management & Business, 2024)
Beyond subtleties, the inimical challenges of corporate working, ratcheting peevish politics, and, needless to say, ignorance of leadership qualities may have unwarranted hostile work environments. This paper intends to analyze it all threadbare.In today's business settings, the combination of office politics and the absence of essential leadership traits can lead to significant issues that negatively impact the performance of organizations and the well-being of employees. Many companies struggle to foster a culture of effective communication and teamwork, often allowing political issues to shape employee behavior and decision-making. Ignoring or overlooking important leadership skills necessary to foster an encouraging and supportive workplace exacerbates this problem. If leaders dont focus on developing these skills, they may unintentionally create an environment filled with confusion and rivalry instead of teamwork. Additionally, the effects of these issues become clearer when looking at different views on corporate meetings and team interactions, as shown in studies about tech workers preferring one-on-one meetings instead of large group ones [citeX]. These preferences highlight the need for leadership that focuses on inclusion and efficiency, which can lead to better teamwork and productivity in organizations.A detailed look at problems in corporate environments shows several key points that highlight how important leadership qualities are and how much political interactions matter. The study finds that not understanding essential leadership traits causes mismanagement and also harms organizational morale and productivity. Furthermore, research demonstrates that external factors such as corruption in global business exacerbate these issues, as companies that fail to recognize the impact of such practices on their strategies often exacerbate their weaknesses ([81]). Furthermore, research on the relationship between multinational companies and resource-rich developing nations reveals that political tactics often overshadow ethical governance, perpetuating inefficiencies within organizations ([82]). In the end, the combination of poor leadership understanding and political involvement stands out as a major challenge, calling for a review of corporate governance structures to promote better and more ethical leadership practices. The theme illustrates the challenges of handling political situations in business.
Keywords: Big Data; Decision Performance; Quality of Decisions; Efficiency of Decisions; Data Analysis; Tunisian Business